Global ruminant production systems found in rangelands - Getahun, Yasin; Flintan, Fiona E. (International Livestock Research Institute, 2018)
This map shows global ruminant production system that exists within rangelands. Selected classes are: LGY (Livestock-only systems in Hyper Arid areas), LGA (Livestock-only systems in arid areas), LGH (Livestock-only systems in humid areas) and LGT (Livestock-only systems in temperate areas or Tropical Highlands). The mapping of global ruminant production systems was undertaken by FAO and ILRI. The mapping of the rangelands is taken from rangeland types and boundaries previously mapped by University of Idaho and the Society for Rangeland Management (SRM). Country boundaries were taken from ESRI 2016.